(3CQHYhf MOjkKG fHhjkGs ((3GHh JeGe CMeO Hf Ydi Hf gOGH GdfGSN GdHZOGOi s)
(3ChdgG (B:s
(3CNHQfG GHh SYjO GdGeOi Yf YHO Gddg Hf YeQ bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B: " (3ef fbd Yfi Edi ef de jdMbfi ef GeJi CQHYjf MOjKkG cJH ai ReQI GdYdeGA hMTQ ai LedI GdTgOGA s
(3BNQgG (B:s
(3hjG hdOi dG JdYHf Hce GdOfjG ceG dYHJ Hi LeYJ GdeGd ef Mdg hef ZjQ Mdg Ke NdaJg dZjQi aGdegfG dg hGdJHYg Ydi aGMPQhG eKd eG Md Hi JeJ GdGQHYjf MOj HMeO Gddg hefg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs